2010
DOI: 10.1111/j.1532-7078.2010.00058.x
|View full text |Cite|
|
Sign up to set email alerts
|

Mental Rotation of Dynamic, Three-Dimensional Stimuli by 3-Month-Old Infants

Abstract: Mental rotation involves transforming a mental image of an object so as to accurately predict how the object would look if it were rotated in space. This study examined mental rotation in male and female 3-month-olds, using the stimuli and paradigm developed by Moore & Johnson (2008). Infants were habituated to a video of a 3-dimensional object rotating back and forth through a 240° angle around the vertical axis. After habituation, infants were tested both with videos of the same object rotating through the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 26 publications
6
95
0
2
Order By: Relevance
“…Possibly, the reason that mental rotation has not often been studied in DS is that it is a very complex spatial skill. Successful rotation strategies are not evident until 4-6 years in TD children (Estes, 1998; Frick, Daum, Walser, & Mast, 2009; Frick, Ferrara, & Newcombe, 2013), although the more basic ability of distinguishing between a figure and its mirror image is observed even in infants as indicated by measures of looking-time (Frick & Möhring, 2013; Moore & Johnson, 2011; Quinn, & Liben, 2008). In a typical mental rotation task the participant looks at an upright figure (e.g., a letter or a design) and then looks at the same figure rotated to different degrees.…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, the reason that mental rotation has not often been studied in DS is that it is a very complex spatial skill. Successful rotation strategies are not evident until 4-6 years in TD children (Estes, 1998; Frick, Daum, Walser, & Mast, 2009; Frick, Ferrara, & Newcombe, 2013), although the more basic ability of distinguishing between a figure and its mirror image is observed even in infants as indicated by measures of looking-time (Frick & Möhring, 2013; Moore & Johnson, 2011; Quinn, & Liben, 2008). In a typical mental rotation task the participant looks at an upright figure (e.g., a letter or a design) and then looks at the same figure rotated to different degrees.…”
Section: Resultsmentioning
confidence: 99%
“…In sharp contrast to research with preschoolers, recent research has shown that infants can discriminate mirror images despite differences in orientation [14][15][16][17][18][19][20][21]. For example, in two such studies [14,15], infants saw an asymmetrical object being moved straight down behind an occluder.…”
Section: Infant Studiesmentioning
confidence: 87%
“…In contrast, infant often see objects in actual physical rotation before the test [16,17,20,21,23,24], or in multiple static orientations [18,19]. This may allow infants to extrapolate motion or to interpolate between familiar views [28].…”
Section: Presentation Of Motion or Multiple Viewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Experiment 1, both age groups showed a strong novelty preference on T1 and a strong familiarity preference on T2. Familiarity preferences are thought to reflect incomplete encoding of a visual stimulus and are typically observed when the stimulus is more complex or the task more demanding (Moore & Johnson, 2011; Rose, Gottfried, Melloy-Carminar, & Bridger, 1982). If infants are given more time to encode the stimulus, familiarity preferences are replaced by novelty preferences (Moore & Johnson, 2011; Roder, Bushnell, & Sasseville, 2000; Rose et al, 1982).…”
Section: Discussionmentioning
confidence: 99%